The (in)visibility of the brazilian movies under the neoliberal globalization - Hettwer, Henrique Rudolfo (Geosaberes, 2019)
This study stems from discussions about the social and productive structure of Brazilian cinema, with specialists and filmmakers. Of the concerns raised about the reduced visibility of the national audiovisual by the population, there was the theoretical basis in the historical and geographic context of neoliberal capital. The multinationals control the Brazilian cinematographic distribution and advance considerably on the production and the exhibition, with omission of the national State, that still facilitated its penetration. Thus, the Brazilian imaginary was not reproduced on canvas and the efforts of countless national talents were vilified. The result: low visibility of the Brazilian film, increased ticket prices, low popular access, growing foreign domination in distribution and exhibition, distinctly from the 1970s, when the state encouraged national cinema through of Embrafilme.